Choreography in the art education system: modern Ukrainian and world practice - Olga Bigus; Dmytro Bazela; Alina Pidlypska; Olha Bilash; Svitlana Yefanova; Nataliia Khodakivska (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.